Implementasi Kerbau Sibandika dalam Meningkatkan Prestasi Belajar Jurnal Penyesuaian pada Siswa Kelas X Akuntansi SMK Negeri 1 Lebakbarang Kabupaten Pekalongan - Fatchurrochman (Jurnal Pendidikan Indonesia, 2022)
The paradigm shift in Student Centered Learning at SMK Negeri 1 Lebakbarang requires significant and continuous efforts through teacher innovation and creativity in the learning process. The majority of students of SMK Negeri 1 Lebakbarang still have the mindset that the teacher is the main actor in learning (teacher centered learning). This has implications for dependence on high teachers and causes student learning outcomes to not meet classical completeness. The author innovates through best practice in the form of Buffalo Sibandika (Auxiliary Paper for Prepaid Adjustments) in order to instill understanding in students about the concept of adjusting prepaid accounts. This Best Practice (best practice) is carried out by the authors in class X AKL 2 in order to improve student learning outcomes. Learning outcomes using the Kebaru Sibandika teaching aid are able to increase students' understanding of prepaid adjustments so as to improve student learning outcomes. This can be seen from the classical completeness and individual mastery of students.